Thiophene sulfonyl electrolyte additive, electrolyte and lithium ion battery

By adding thiophenesulfonyl electrolyte additive and FEC to the electrolyte of lithium-ion batteries, the film-forming impedance and cycling performance of the battery are solved, and the impedance deterioration of the battery when using silicon-based negative electrode materials is improved, achieving the improvement of the high-temperature and high-voltage cycling performance of the battery.

CN119674240APending Publication Date: 2025-03-21安徽得壹能源科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411852051.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When using silicon-based negative electrode materials in existing lithium-ion batteries, the high content of FEC in the electrolyte will increase the thickness of the SEI and CEI films, causing the battery impedance to deteriorate and affect the battery's cycling performance.

Method used

The thiophenesulfonyl electrolyte additive is used, and the high temperature and high voltage cycle performance of the battery is improved by adding 0.1%-3% of the thiophenesulfonyl electrolyte additive and 1%-9% of FEC to the electrolyte.

Benefits of technology

Effectively improve the DCR of lithium-ion batteries, improve the power performance and cycle life of the battery, and significantly improve performance under high temperature and high voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674240A_ABST
    Figure CN119674240A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolyte additives, and discloses a thiophenesulfonyl electrolyte additive, an electrolyte and a lithium ion battery, the thiophenesulfonyl electrolyte additive has the following structural formula: # imgabs0 #, in which R1 is selected from F, H or sulfonyl fluoride; r2 is selected from F, H or sulfonyl fluoride; r3 is selected from F, H or sulfonyl fluoride; and R1, R2 and R3 at least comprise one fluorine atom. Through the synergistic effect of the thiophenesulfonyl electrolyte additive and the FEC, the positive and negative electrode film-forming impedance can be effectively improved, the side reaction is inhibited, and the high-temperature and high-voltage cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolyte additives, and in particular relates to a thiophenesulfonyl electrolyte additive, an electrolyte and a lithium ion battery. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] In order to increase the driving range of new energy vehicles and the single-charge usage time of 3C products, how to improve the energy density of lithium-ion batteries has always been the focus of research in the industry. Currently, commercial high-energy-density lithium-ion battery systems mainly use high-nickel or high-voltage positive electrode materials (LiNi x Co y Mn (1-x-y) O2) matches silicon-based negative electrode materials (SiO x , SiC, etc.), since the volume expansion of silicon-based negative electrode materials during charging and discharging will cause repeated growth of SEI, therefore, it is necessary to ensure the presence of consumable film-forming additives in the electrolyte to support the long cycle performance of the battery.

[0004] Fluoroethylene carbonate (FEC) is a common electrolyte additive, which forms a dense SEI (solid-electrolyte membrane) rich in LiF at the negative electrode. Good mechanical strength can effectively improve the cycle performance of silicon-based negative electrode batteries. The content of FEC in the electrolyte is positively correlated with the mass proportion of silicon-based materials in the negative electrode. For example, if the silicon-based material accounts for 10%, the proportion of FEC in the electrolyte needs to reach more than 5%. However, FEC will not only generate LiF but also ethylene carbonate (EC) during the film formation process of the negative electrode, and EC will further polymerize to cause the thickness of SEI and CEI to continue to increase, causing the battery impedance to deteriorate seriously. Sulfonic acid compounds (such as DTD, MMDS, etc.) and thiophene compounds (thiophene, 2-thiophenecarbonitrile, etc.) have the characteristics of low film formation impedance and have achieved good results in high energy density lithium-ion batteries. However, for battery systems using silicon-based negative electrodes, they still need to be used in conjunction with FEC, and the mass percentage of FEC in the electrolyte during the use process still needs to be greater than 5%, so the above problems still exist. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a thiophenesulfonyl electrolyte additive, an electrolyte and a lithium ion battery.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a thiophenesulfonyl electrolyte additive, the structural formula of which is shown below:

[0008]

[0009] Wherein, R1 is selected from F, H or sulfonyl fluoride; R2 is selected from F, H or sulfonyl fluoride; R3 is selected from F, H or sulfonyl fluoride; and at least one fluorine atom is included in R1, R2 and R3.

[0010] In some embodiments, the thiophenesulfonyl electrolyte additive is at least one selected from the following compounds:

[0011]

[0012]

[0013] Preferably, the thiophenesulfonyl electrolyte additive is selected from: or

[0014] In a second aspect, the present invention provides a method for preparing the thiophenesulfonyl electrolyte additive, comprising the following steps:

[0015] The KF solution is heated to 40° C.-75° C., and then the chlorothiophenesulfonyl compound solution is added thereto in batches so that the molar ratio of the chlorothiophenesulfonyl compound to KF is 1:1-5;

[0016] After the addition is complete, continue the reaction for 1-3 hours;

[0017] After the reaction is completed, the product is purified to obtain a thiophenesulfonyl electrolyte additive.

[0018] In some embodiments, the solvent in the KF solution and the chlorothiophenesulfonyl compound solution is DMC (dimethyl carbonate).

[0019] In some embodiments, the duration of adding the chlorothiophenesulfonyl compound solution is 60 min-70 min.

[0020] In the second aspect, the present invention provides an electrolyte, including a lithium salt, a solvent, FEC (fluoroethylene carbonate) and the thiophenesulfonyl electrolyte additive, wherein the mass percentage of the thiophenesulfonyl electrolyte additive in the electrolyte is 0.1%-3%, and the mass percentage of FEC is 1%-9%, preferably 2%-5%. The main function of FEC in silicon-containing negative electrode batteries is to generate a SEI film with LiF as the main component, which is more stable than organic components. During the battery cycle, the volume of the silicon negative electrode expands greatly, and a new interface will be generated, which will be accompanied by the continuous generation of SEI. If the FEC content is too little, the battery cycle life will be seriously deteriorated.

[0021] The synergistic effect of the two additives can effectively improve the film formation impedance of the positive and negative electrodes, inhibit side reactions, and enhance the high temperature and high voltage cycle performance of the battery.

[0022] In some embodiments, the amounts of the thiophenesulfonyl electrolyte additive and FEC satisfy the following conditions: 0.005*m≤n*x / M+y / 106≤0.008;

[0023] Wherein, n is the number of F atoms in the thiophenesulfonyl electrolyte additive compound molecule;

[0024] M is the molecular weight of the thiophenesulfonyl electrolyte additive compound;

[0025] m is the mass percentage of silicon-based material in the negative electrode main material;

[0026] x is the mass percentage of the thiophene-based additive in the electrolyte, which ranges from 0.1% to 3%, preferably from 0.5% to 2%;

[0027] y is the mass proportion of FEC in the electrolyte, which ranges from 1% to 9%, preferably from 2% to 5%.

[0028] Preferably, the negative electrode main material comprises a silicon-based material and a graphite material, and the silicon-based material is selected from silicon oxide (SiO x ), at least one of pre-lithium or pre-magnesium silicon oxide, carbon-coated nanosilicon or porous carbon vapor deposited silicon (third generation SiC).

[0029] In some embodiments, the mass percentage of the thiophenesulfonyl electrolyte additive in the electrolyte is 1%-2%.

[0030] In some embodiments, the mass percentage of the lithium salt in the electrolyte is 10%-20%, preferably 12%-16%.

[0031] Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate)phosphate (LiDFOP) or lithium tetrafluorooxalatephosphate (LiTFOP).

[0032] In some embodiments, the mass percentage of the solvent in the electrolyte is 70%-88%, preferably 75%-85%.

[0033] Preferably, the solvent is selected from two or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), γ-butyrolactone (GBL), ethyl acetate (EA), methyl acetate (MA), propyl acetate (PA), methyl propionate (MP), propyl propionate (PP), and ethyl propionate (EP).

[0034] In some embodiments, the electrolyte further includes other additives, and the other additives are selected from at least one of ethylene sulfite (ES), 1,3-propane sultone (PS), tris(trimethylsilyl) phosphate (TMSP), succinonitrile (SN), adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTCN), 1,2-bis(2-cyanoethoxy)ethane (DENE), tripropargyl phosphate, triallyl phosphate, tris(2-cyanoethyl) phosphate, tripropargyl phosphite, triallyl phosphite, tris(2-cyanoethyl) phosphite, tripropargyl borate, triallyl borate, and tris(2-cyanoethyl) borate.

[0035] Preferably, the mass percentage of other additives in the electrolyte is 0.2%-3%.

[0036] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte.

[0037] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0038] 1. The inventors proposed a F-containing thiophenesulfonyl compound as an electrolyte additive based on the performance requirements of lithium-ion batteries with silicon-based negative electrodes and lithium cobalt oxide positive electrodes or ternary materials. The compound contains at least one F atom, which participates in the negative electrode film formation, especially on the surface of the silicon-based material, to form a stable SEI film rich in a large amount of LiF. The thiophene group and sulfonyl group in the compound can also participate in the positive and negative electrode film formation. The SEI or CEI rich in the above components has good conductivity. Compared with the solution of using only FEC, the battery DCR can be effectively improved when used in combination with FEC, thereby improving the power performance and cycle life of the battery.

[0039] 2. The inventors have obtained through several experiments the relationship between the amount of thiophenesulfonyl compound and FEC added to the electrolyte and the mass proportion of the silicon-based negative electrode in the negative electrode active material of the battery using the electrolyte. The electrolyte configured according to the relationship has achieved good results in practical applications;

[0040] 3. The present invention also provides a method for synthesizing F-containing thiophenesulfonyl compounds. The method has a wide range of raw material sources, a short process path, and a high yield, and has a wide range of use value for the industrial production of such additives. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0042] The present invention will be further described below in conjunction with the embodiments.

[0043] Example

[0044] The synthesis method of 2-thiophenesulfonyl fluoride comprises the following steps:

[0045] 1) dissolving 36.5 g of 2-thiophenesulfonyl chloride in 100 g of high-purity DMC (purity ≥ 99.95%) and mixing well to obtain a mixed solution A;

[0046] 2) 14.0 g of micron-sized KF powder (D 50 =1.5 μm) was added into 52.0 g of high-purity DMC to obtain a mixed solution B;

[0047] 3) Add the mixed solution B to a 500 mL three-necked flask equipped with a reflux device, heat to 65°C, and after the temperature in the three-necked flask stabilizes, add the mixed solution A dropwise at a uniform rate, control the entire dropping process time to be 60 minutes, and continue heating the reaction for 2 hours after the addition is completed;

[0048] 4) After filtering the reaction mixture, molecular distillation was performed to obtain 18.4 g of thiophenesulfonyl fluoride with a purity greater than 99.5%, and the overall yield was 55.8%.

[0049] The thiophenesulfonyl compounds involved in the present invention can be prepared by the above preparation method, and the molar ratio of the reactants can be adjusted under the premise of maintaining a certain ratio (1:1-5) of the Cl-containing thiophenesulfonyl compound and KF. For example, when 4,5-dichloro-2-thiophenesulfonyl fluoride is used to prepare 4,5-difluoro-2-thiophenesulfonyl fluoride, the molar ratio of KF to 4,5-dichloro-2-thiophenesulfonyl fluoride should be kept greater than 2, and the reaction temperature (40°C-75°C) and time should be adjusted to obtain a higher yield of the target product.

[0050] The present invention also relates to a lithium ion battery using the electrolyte containing the thiophenesulfonyl compound, and the specific preparation process is as follows:

[0051] Preparation of positive electrode sheet: polyvinylidene fluoride (PVDF), conductive agent (Super P) and carbon tube (CNT), single crystal LiNi7Co1Mn3O2 are added to N-methylpyrrolidone (NMP) at a mass ratio of 1.2%: 0.5%: 0.5%: 97.8%, mixed evenly to form slurry, and coated on aluminum foil current collector. The single surface density of positive electrode is 220±3g / m 2 , cold pressed to 4.1g / m 3 , and the positive electrode sheet is obtained after punching.

[0052] Preparation of negative electrode sheet: Sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene-butadiene rubber latex (SBR), conductive agent (Super P), single-walled carbon tube (SWCNT), negative electrode active material (third-generation silicon: artificial graphite mass ratio 8:92) are added into deionized water at a mass ratio of 0.4%: 1.6%: 0.8%: 0.94%: 0.06%: 96.2%, and the mixture is stirred and mixed evenly. The slurry is coated on the copper foil current collector, and the negative electrode surface density is determined according to the N / P ratio of 1.06, and the cold pressing is performed to 1.55g / m 3 , and then punch out to make the negative electrode sheet.

[0053] Configuration of the electrolyte: LiPF6 is selected as the lithium salt, and its content is 14% of the total mass of the electrolyte; ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are used as the solvent, and the mass ratio is 3:7. The type and amount of additives used are shown in Table 1. The entire configuration process is completed in a glove box with a moisture content of <1ppm.

[0054] Preparation of battery: stack the separator, negative electrode and positive electrode in a "Z" shape to obtain the bare battery to be injected, then use aluminum plastic film to package the battery to be injected, and after baking, obtain the battery to be injected. The designed capacity of the battery to be injected is 5Ah. According to the injection coefficient of 2.6g / Ah, 13g of electrolyte is injected into the battery to be injected. After formation, it is placed at 45℃ for 48h and then charged and discharged 3 times with a current of 1C in the voltage range of 2.8V to 4.4V to obtain the battery to be tested.

[0055] Lithium-ion battery testing:

[0056] DCR test: Charge the battery to 4.0V with constant current and constant voltage. After standing for 6 hours, test the DC internal resistance of the battery under 2C charging.

[0057] Rate charging performance test: Charge the battery to 4.4V at 1C and 3C constant current and constant voltage, with a cut-off current of 0.05C, and discharge it to 2.8V at 1C, and calculate the constant current charging capacity ratio.

[0058] High temperature storage performance test: The fully charged battery is stored at 40°C for 30 days to test the capacity retention rate and capacity recovery rate.

[0059] Normal temperature / high temperature cycle performance test: The capacity retention rate under different number of 1C charge and discharge cycles was tested at 25℃ and 45℃ respectively. The charge and discharge cut-off voltage was 2.8V~4.4V, and the constant voltage charge cut-off current was 0.05C.

[0060] The test data of the embodiments and comparative examples are shown in Table 2.

[0061] Table 1

[0062]

[0063] Table 2

[0064]

[0065]

[0066] Comparative Examples 1 to 3 are single-factor variable experiments on the amount of FEC added. The results show that, under the test battery system, an increase in FEC content is beneficial to the 25°C cycle performance, but the DCR, high-temperature cycle and fast charging performance are seriously deteriorated. This is mainly due to the increase in polycarbonate components in the CEI / SEI membrane under high FEC content; although the battery has a certain improvement in high-temperature performance at a lower FEC content, the 25°C cycle performance will be affected. From the comprehensive performance point of view, under this battery system, the electrolyte solution with 6% FEC content is more excellent.

[0067] In Example 1 and Example 2, compared with Comparative Example 1, 2% of different thiophenesulfonyl compounds are used to replace FEC in equal proportions. From the test data, it can be seen that the overall performance of the battery is improved to a certain extent. It can be seen that after the thiophene group and the sulfonyl group participate in the film formation, not only the film formation impedance can be reduced, but also the interface stability is improved, especially the positive / negative electrode interface side reactions at high temperatures are well inhibited.

[0068] Compared with Example 1, the room temperature and high temperature cycles of the battery in Example 2 are improved to a certain extent. By comparing the structures of 2-thiophenesulfonyl fluoride and 4,5-difluoro-2-thiophenesulfonyl fluoride, it is easy to infer that the F content in the compound (or the proportion of F atoms per unit mass) has an important influence on the battery cycle performance.

[0069] Compared with Example 2, Example 3 and Example 4 reduce the FEC content while keeping the 4,5-difluoro-2-thiophenesulfonyl fluoride content in the electrolyte unchanged. From the battery performance comparison, it can be found that reducing the FEC content can significantly improve the battery DCR, fast charging performance and high temperature storage performance, but it can also be seen that too low FEC content will cause the deterioration of the battery cell cycle performance. Based on Example 4, under the premise of fixing the FEC content, the gradient performance of the 4,5-difluoro-2-thiophenesulfonyl fluoride content was verified.

[0070] Compared with Example 4, the DCR and fast charging performance of the battery using the solution in Example 6 are slightly improved, and other performances remain at a considerable level. Therefore, when designing the electrolyte solution, it is necessary to balance the demand for thiophenesulfonyl compounds for SEI / CEI film formation and the impact of increased battery viscosity due to increased addition of thiophenesulfonyl compounds on battery performance.

[0071] Considering that both thiophenesulfonyl compounds and DTD participate in film formation through sulfonyl groups, Examples 7 and 8 were compared with Example 6 to test the DTD content. It was found that the overall performance of the battery in Example 7 was almost equivalent to that in the reference. Therefore, it can be inferred that after adding thiophenesulfonyl compounds to the electrolyte, the amount of DTD used can be reduced to a certain extent, thereby achieving the purpose of reducing the cost of the electrolyte.

[0072] Table 3

[0073]

[0074] In order to achieve fast and accurate electrolyte formula design, several experiments were conducted for different silicon-based negative electrodes, different positive electrode materials, and different proportions of silicon-based materials in negative electrode active materials. Through a large number of experiments, it was found that the amount of thiophenesulfonyl compounds and FEC added to the electrolyte is closely related to the mass proportion of silicon-based negative electrodes in the negative electrode active materials of the battery using the electrolyte. In order to further summarize the rules of the two, a large amount of data statistics were performed on the molar content of F atoms brought into the electrolyte by the two additives. Combined with the proportion of silicon-based materials in the negative electrode main material in the corresponding scheme, the overall rule satisfies 0.005*m≤n*x / M+y / 106≤0.008*m. Taking the embodiments disclosed in this patent as an example (see Table 3), except for Example 2, all meet the above requirements, that is, 0.0004≤n*x / M+y / 106≤0.00064, and Example 2 is not the optimal solution for the electrolyte design of this system. Therefore, the construction of the relationship provides a wide range of use value for the application of thiophenesulfonyl compounds in electrolytes and the design of high energy density lithium-ion battery electrolytes.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thiophenesulfonyl electrolyte additive, characterized in that: Its structural formula is as follows: Wherein, R1 is selected from F, H or sulfonyl fluoride; R2 is selected from F, H or sulfonyl fluoride; R3 is selected from F, H or sulfonyl fluoride; and at least one fluorine atom is included in R1, R2 and R3.

2. The thiophenesulfonyl electrolyte additive according to claim 1, characterized in that: The thiophenesulfonyl electrolyte additive is at least one selected from the following compounds: Preferably, the thiophenesulfonyl electrolyte additive is or 3. The method for preparing the thiophenesulfonyl electrolyte additive according to claim 1 or 2, characterized in that: The steps include: The KF solution is heated to 40° C.-75° C., and then the chlorothiophenesulfonyl compound solution is added thereto in batches so that the molar ratio of the chlorothiophenesulfonyl compound to KF is 1:1-5; After the addition is complete, continue the reaction for 1-3 hours; After the reaction is completed, the product is purified to obtain a thiophenesulfonyl electrolyte additive.

4. The method for preparing the thiophenesulfonyl electrolyte additive according to claim 3, characterized in that: The duration of adding the chlorothiophenesulfonyl compound solution is 60 min-70 min.

5. An electrolyte, characterized in that: It comprises lithium salt, solvent, FEC and the thiophenesulfonyl electrolyte additive according to claim 1 or 2, wherein the mass percentage of the thiophenesulfonyl electrolyte additive in the electrolyte is 0.2%-3%, and the mass percentage of FEC is 1%-9%, preferably 2%-5%.

6. The electrolyte according to claim 5, characterized in that: The dosage of the thiophenesulfonyl electrolyte additive and FEC satisfies the following conditions: 0.005*m≤n*x / M+y / 106≤0.008; Wherein, n is the number of F atoms in the thiophenesulfonyl electrolyte additive compound molecule; M is the molecular weight of the thiophenesulfonyl electrolyte additive compound; m is the mass percentage of silicon-based material in the negative electrode main material; x is the mass percentage of the thiophene-based additive in the electrolyte, which ranges from 0.1% to 3%, preferably from 0.5% to 2%; y is the mass proportion of FEC in the electrolyte, which ranges from 1% to 9%, preferably from 2% to 5%. Preferably, the negative electrode main material comprises silicon-based material and graphite material, and the silicon-based material is selected from at least one of silicon oxide, pre-lithium or pre-magnesium silicon oxide, carbon-coated nano-silicon or porous carbon vapor-deposited silicon.

7. The electrolyte according to claim 5, characterized in that: The mass percentage of the thiophenesulfonyl electrolyte additive in the electrolyte is 1%-2%; Or, the mass percentage of the lithium salt in the electrolyte is 10%-20%, preferably 12%-16%; Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorobis(oxalate)phosphate or lithium tetrafluorooxalatephosphate.

8. The electrolyte according to claim 5, characterized in that: The mass percentage of the solvent in the electrolyte is 70%-88%, preferably 75%-85%; Preferably, the solvent is selected from two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, ethyl acetate, methyl acetate, propyl acetate, methyl propionate, propyl propionate and ethyl propionate.

9. The electrolyte according to claim 5, characterized in that: The electrolyte further comprises other additives, and the other additives are selected from at least one of vinyl sulfite, 1,3-propane sultone, tris(trimethylsilane) phosphate, succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2-bis(2-cyanoethoxy)ethane, tripropargyl phosphate, triallyl phosphate, tris(2-cyanoethyl) phosphate, tripropargyl phosphite, triallyl phosphite, tris(2-cyanoethyl) phosphite, tripropargyl borate, triallyl borate, and tris(2-cyanoethyl) borate; Preferably, the mass percentage of other additives in the electrolyte is 0.2%-3%.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to any one of claims 5-9.

Citation Information

Cited By

  • Fluorine-containing thiophene compound, preparation method thereof and electrolyte

    CN119899170A

  • Fluorinated thiophene compounds, their preparation methods, and electrolytes

    CN119899170B